Structural Design and Fabrication of Multifunctional Nanocarbon Materials for Extreme Environmental Applications. Issue 52 (30th September 2022) - Wu, Sijia; Li, Huajian; Futaba, Don N.; Chen, Guohai; Chen, Chen; Zhou, Kechen; Zhang, Qifan; Li, Miao; Ye, Zonglin; Xu, Ming
Abstract: Extreme environments represent numerous harsh environmental conditions, such as temperature, pressure, corrosion, and radiation. The tolerance of applications in extreme environments exemplifies significant challenges to both materials and their structures. Given the superior mechanical strength, electrical conductivity, thermal stability, and chemical stability of nanocarbon materials, such as carbon nanotubes (CNTs) and graphene, they are widely investigated as base materials for extreme environmental applications and have shown numerous breakthroughs in the fields of wide‐temperature structural‐material construction, low‐temperature energy storage, underwater sensing, and electronics operated at high temperatures. Here, the critical aspects of structural design and fabrication of nanocarbon materials for extreme environments are reviewed, including a description of the underlying mechanism supporting the performance of nanocarbon materials against extreme environments, the principles of structural design of nanocarbon materials for the optimization of extreme environmental performances, and the fabrication processes developed for the realization of specific extreme environmental applications. Finally, perspectives on how CNTs and graphene can further contribute to the development of extreme environmental applications are presented. Abstract : Nanocarbon materials such as carbon nanotubes and graphene have provided a variety of unique extreme environmental properties. The recent advances on nanocarbon materials for extreme environments are summarized from the feature of individual nanocarbon components, principles of structural design, fabrication technologies, while examples of their extreme environmental applications with the underlying working mechanism are given.